The 2017 EULAR standardised procedures for ultrasound imaging in rheumatology. Issue 12 (16th August 2017) - Möller, Ingrid; Janta, Iustina; Backhaus, Marina; Ohrndorf, Sarah; Bong, David A; Martinoli, Carlo; Filippucci, Emilio; Sconfienza, Luca Maria; Terslev, Lene; Damjanov, Nemanja; Hammer, Hilde Berner; Sudol-Szopinska, Iwona; et al.
Abstract : Background: In 2001, the European League Against Rheumatism developed and disseminated the first guidelines for musculoskeletal (MS) ultrasound (US) in rheumatology. Fifteen years later, the dramatic expansion of new data on MSUS in the literature coupled with technological developments in US imaging has necessitated an update of these guidelines. Objectives: To update the existing MSUS guidelines in rheumatology as well as to extend their scope to other anatomic structures relevant for rheumatology. Methods: The project consisted of the following steps: (1) a systematic literature review of MSUS evaluable structures; (2) a Delphi survey among rheumatologist and radiologist experts in MSUS to select MS and non-MS anatomic structures evaluable by US that are relevant to rheumatology, to select abnormalities evaluable by US and to prioritise these pathologies for rheumatology and (3) a nominal group technique to achieve consensus on the US scanning procedures and to produce an electronic illustrated manual (ie, App of these procedures). Results: Structures from nine MS and non-MS areas (ie, shoulder, elbow, wrist and hand, hip, knee, ankle and foot, peripheral nerves, salivary glands and vessels) were selected for MSUS in rheumatic and musculoskeletal diseases (RMD) and their detailed scanning procedures (ie, patient position, probe placement, scanning method and bony/other landmarks) were used to produce the App. In addition, US evaluable abnormalities present in RMD for each anatomic structure and their relevance for rheumatology were agreed on by the MSUS experts. Conclusions: This task force has produced a consensus-based comprehensive and practical framework on standardised procedures for MSUS imaging in rheumatology.